La Matriz de Capacidades y Desempeños (MCD) y el Algoritmo del Desarrollo Humano (ADH) - Gonzales de Olarte, Efraín (2010)
Given that human development is a complex process involving multiple components and determiningfactors, multidimensional indicators are needed. On the basis of the extensive literatureon the subject, we advance two new indicators: the Matrix of Capabilities and Functioning (MCF), and the Algorithm of Human Development (HDA). The MCF is composed of vectors of capabilities and functionings, based on Sen’s idea of Refined Functionings. It is based in a matricial framework, both static and dynamic. The main purposeof constructing this index is to study how different sets of capabilities relate to alternative functionings, to produce diverse outcomes. The Human Development Algorithm (HAD) is a multidimensional index concerning the setof goods and services needed to complete a life cycle. The HDA is a socio-economic contextindicator. It is composed of the main «satisfactors» or basic goods and services needed: food, health, education, housing, social security, decent employment and retirement programs, thatmight be available to all throughout of life cycle. This indicator shows the material progress reached by each country or region as well the institutional organization, private and public, and the degree of social cohesion and solidarity.